FORMULASI SEDIAAN PASTA GIGI KARBON AKTIF DENGAN BASIS Virgin Coconut Oil (VCO) - Imas Maesaroh; Silva Silviani (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2019)
Activated carbon is defined as carbon that has a great absorptive capacity of anions, cations, and molecules in the form of organic and inorganic compounds, either in the form of solutions or gases. Activated carbon has been highly used for various things, mainly to absorb dirt or toxins. The pores formed on this activated carbon will bind the impurities on the tooth surface. Therefore, cleaning the yellowish substances on the teeth will be easier. The aim of this research is to make dentifrice formulation with variety of activated carbon concentrate as the active substance and Virgin Coconut Oil (VCO) as the basis to get best tooth paste formula, or to meet toothpaste quality requirement.The concentrate of activated carbon used was12.5%, 15%, 17.5%, 20% and the Virgin Coconut Oil (VCO) concentrate used was 10%, 12.5%, 15%, 17.5% , 20%. Other additives that were also used were calcium carbonate, sorbitol, glycerol, Na.CMC, saccharin, sodium benzoate, sodium lauryl sulphate, menthol and aquades. The result of research indicated that the nifty basis of VCO was F3 with 15% VCO concentrate and 15% of F1 activated carbon toothpaste formula, which fulfilled toothpaste quality requirement. This formula was used to test gray organoleptic test, delicate texture, and homogeneous. It also had a pH of 8 which was corresponding to the pH value requirement for dentifrice preparations according to SNI 12-3524-1995 ie 4.5 -10.5 and typical menthol odor and fresh taste. The toothpaste does not contain of air bubbles, separated lumps and particles, and foreign objects are not visible.